Optimal irrigation scheduling for off-season vegetable crops in Côte d'Ivoire - CGIAR Research Program on Rice (2020)
We are developing an optimal irrigation scheduling to increase off-season vegetables yield and water productivity. Data of two seasons study showed that irrigation every 3 days resulted in the highest yield and water productivity for tomato and cucumber.